1413. Trends in Risk of Respiratory Syncytial Virus Hospitalizations in Preterm Infants Over a 10-Year Period. (31st December 2020) - Kong, Amanda M; Winer, Isabelle H; diakun, david; Bloomfield, Adam; Gonzales, Tara
Abstract: Background: The American Academy of Pediatrics (AAP) recommended respiratory syncytial virus (RSV) immunoprophylaxis (RSV-IP) to reduce the risk of severe RSV hospitalization (RSVH) for certain infants < 35 weeks gestational age (wGA) until 2014, when the AAP no longer recommended use among infants born >29 wGA without other medical conditions. Studies have shown that RSV-IP utilization subsequently decreased among these infants, as well as infants born < 29 wGA from whom RSV-IP is still currently recommended. We described RSVH rates among preterm (PT) infants < 35 wGA compared to term infants from 2008-2019. Methods: We identified infants born between 7/1/2008 and 7/30/2019 in the MarketScan® Commercial and Multi-State Medicaid claims databases. Infants with a code for birth at < 35 wGA were classified by wGA. Those with a code for full-term without major health problems were classified as term. Infants contributed follow-up time during the RSV season (November to March) while < 6 months old, summarized as infant-seasons (days of follow-up during the RSV season divided by 151 [number of days in an RSV season]) (Table 1). Using diagnoses codes, we identified RSVH during each RSV season for infants < 6 months. Unadjusted rate ratios comparing PT infants to term infants were calculated to account for seasonal variation in virus circulation. Number of Infants and Follow-up Time Results: The number of infants contributing time at < 6 months old during the RSV season and their follow-up time are shown in Table 1. There were 796 RSVH among Commercial PT infants, 6, 486 RSVH among Commercial term infants, 2, 501 RSVH among Medicaid PT infants, and 13, 962 RSVH among Medicaid term infants during the 10 seasons in the database. RSVH rates for PT infants tended to increase over time, with the exception of the 2009-2010 season for Medicaid infants (Table 2). Rate ratios comparing PT to term infants also increased after the 2014 guidance change (Figure 1 and 2). The risk of 29-34 wGA infants compared to term infants approximately doubled in the 5 years after the guidance change (Table 2). Comparisons of RSV Hospitalization Rates for Preterm vs. Term Infants < 6 Months Old Rate Ratios for RSV Hospitalization Rates for Commercial Infants < 6 Months Old Rate Ratios for RSV Hospitalization Rates for Medicaid Infants < 6 Months Old Conclusion: After the change in AAP recommendations for RSV-IP, increases in RSVH rates for infants born at 29-34 wGA compared to term were found. This was also true for < 29 wGA infants for whom RSV-IP is recommended, although the effect sizes were smaller. Disclosures: Amanda M. Kong, DrPH, Sobi (Other Financial or Material Support, I am an employee of IBM Watson Health which received funding from Sobi to conduct this analysis.) david diakun, BS, Sobi (Grant/Research Support) Adam Bloomfield, MD, Sobi NA (Employee) Tara Gonzales, MD, Sobi, Inc. (Employee)